The Incidences of Use the Over Counter Drugs - Abeerfadhil Ibraheem (Journal of Global Pharma Technology, 2018)
Importance of the study:  over-the-counter (OTC) medication is commonly used, among older, adults and children. They can be dangerous because their side effect, interactions with other medication and allergic reactions. The most OTC medications frequently utilized worldwide are Paracetamol (acetaminophen), Non-steroidal anti-inflammatory drugs (NSAID), stomach upset, antitussive, allergy and skin rashes and itching medications. Objectives:  To determine the misused practice of over-the-counter medications, to assess the common use of the over-counter medication and to assess patient's information about commonly used over-the-counter (OTC) medication. Design, Setting, and Participants:  Descriptive analyses study, the sample was (100) participants, conducted from community-dwelling from 21 to 61and over years old male and female. Using assessment tool instructed from literature review from1/2/2018-1/3/2018, the reliability of the questionnaire through the use of Cronbach's Alpha was (.846). Results:  the study revealed that the lowest mean score (1.53) for knowing how much weights before giving these medicines. The lowest mean score (1.73) for they check with care provider before taking an (OTC) when having a long-term medical problem or are taking prescription medicines, the lowest mean score (1.3) for they taking acetaminophen every 4 to 6  to relieve headache, fever & pain. Conclusions : the most  of study sample didn’t aware about the weight  and the dose of taking medication, check with care physician before taking an over-the-counter drugs when having a long-term medical treatment or dealing with prescription therapies and when they taking acetaminophen every 4 to 6  to relieve headache, fever & pain .Keywords:  Over counter medication (OTC), Misuse, Non-steroidal anti-inflammatory drugs (NSAIDs) and stomach upset.